A tailored phytosomes based nose-to-brain drug delivery strategy: Silver bullet for Alzheimer's disease - Xiao Yue; Haihua Guo; Guanlin Wang; Jieyun Li; Zizhao Zhai; Zeting Wang; Wenhao Wang; Ziyu Zhao; Xiao Xia; Chuangxin Chen; Yingtong Cui; Chuanbin Wu; et al. (Bioactive Materials)
With the aging of the population, the incidence of Alzheimer's disease (AD) has increased dramatically, causing severe medical, care, and economic burdens on society and families. The efficacy of rivastigmine hydrogen tartrate (RHT), the first-line clinical treatment, is severely limited by the complex and multiple pathogenesis of AD and low brain bioavailability caused by the blood-brain barrier (BBB). Confronting such two bottlenecks, the development of multi-target agents encapsulated BBB-bypassing drug delivery systems offer tremendous therapeutics possibilities for AD. In this study, a tailored phytosomes based nose-to-brain drug delivery system with appropriate plume was successfully designed and developed. On the one hand, Ginseng RG3-based phytosomes loaded with RHT was designed for the co-delivery of GRg3 and RHT, achieving the multi-target pharmacology for AD treatment. On the other hand, a tailored nose-to-brain drug delivery system was established for the satisfactory nose-to-brain delivery efficiency, avoiding the obstacle of BBB through bypassing it. In the pharmacodynamic study based on AD rat model, GRg3@RHT exhibited obviously synergic effect, effectively break the vicious cycle of AD progression, ultimately markedly ameliorating learning and memory ability as well as behavioral dysfunctions, and delaying the neurodegenerative process associated with AD. In addition, the strong correlation of viscosity-droplet size-plume geometry-olfactory deposition was also established, and further proved by the in vivo pharmacokinetic study, which is proposed to provide evidence to enhance nose-to-brain delivery efficiency. This study is anticipated to provide novel insights into AD treatment strategies while offering innovative ideas for drug delivery approaches targeting nervous system disorders.